REPRESENTING VOICES IN TOURISM – CROSS-CULTURAL ANALYSES - Petrovska, Irina (Horizons - International Scientific Journal, 2020)
The main objective of this paper is through analysis and description of the language of tourism in the English and Macedonian to evaluate similarities and differences in the tourism communication and to highlight their cultural aspects. The accent is put on differences and similarities of both cultures that have their own realization through language interactions, where the subcultures and individual variables that motivate people to speak as they do, are deeply integrated. Following the basic principles of the ethnography of communication and its key components that are part of language interactions, the ethnographies observed showed existence of certain culturally specific similarities and differences in the communicative competence   of the speakers of both languages. The differences in the ethnographies in the English and Macedonian language are due to the fact that the cultural systems of both languages are organized differently.